Dampak COVID-19 Terhadap Pelayanan KIA di Kabupaten Tangerang - Puspitasari, Dewi Ayu; Pratomo, Hadi; Sudiarti, Trini; Indriyani, Sri (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: The COVID-19 pandemic response is affecting maternal and Child health services in Indonesia including Kabupaten tangerang. This study aimed to identify the impact of COVID-19 on MCH services in Kabupaten Tangerang.Methods: This article used a mixed-method study with deductive sequential design. The quantitative data was obtained from routine data on the PulihCovid dashboard, while the qualitative data was obtained from in-depth interviews with responsible officers in Dinas kesehatan Kabupaten Tangerang.Results: In general, there was a decrease in the number of visits by pregnant women in 2020 compared to the previous year starting in April, one month after the first positive cases of COVID-19 appeared in Kabupaten Tangerang. In line with this, there has been an increase in the number of maternal deaths due to COVID-19. To overcome this, the Tangerang District Health Office uses WhatsApp and selular in conducting education and morning assistance for pregnant women during the COVID-19 pandemic.Conclusion: The recommendation proposed in this study are to improve the referral system for pregnant women and improve delivery facilities for pregnant women with COVID-19.